TÜRK DİZİLERİNİN KAZAK-TÜRK KÜLTÜREL ETKİLEŞİMİNE VE TÜRKÇENİN YAYGINLAŞMASINA ETKİSİ. - ARBATLI, Mehmed Said; KURAR, İhsan (Electronic Turkish Studies)
Objective of the Study: In the present era, dizzying developments in the transportation and communication facilities changed the world into a global village and made different societies closer each other ever than before. This approach naturally brought intercultural interaction together. It is a fact that dominant culture affects the other culture(s) when there is a mutual interaction. Today cultural dominance means the ability to show, promote and market - so to say, its own culture, communication instruments and methods better than each other. Republic of Turkey is rapidly advancing to become an important element of power and balance in its region thanks to its developments in all fields. Turkey has realized serious advance with regard to expansion to the world and it is known that Turkish TV series play important roles for boosting the promotion and popularity of Turkey serving like a cultural envoy and a window to outer world. These productions are called as the Â"soft powerÂ" of Turkey by numerous researchers and are in a position to provide great contributions to the promotion of Turkish language and culture. Several Turkish TV series have been broadcast in Kazakhstan for years and there are also many people watching them over the Internet. However, there have been no academic studies regarding the effects of the concerned TV series on the promotion of Turkey and Turkish culture and on the spread of Turkish language as spoken in Turkey. The relations between Turkey and Kazakhstan are very important for both countries with respect to economic, political and strategic aspects as well as historic and cultural ties. Therefore, this study is necessary to fill in a gap in its field. The objective of this study is to determine the said effects of the Turkish TV series specifically in Kazakhstan and to bring proposals on this matter. Method of the Study: The basic data collection means of the study was a questionnaire form which was developed to measure the effects of Turkish TV series on cultural interaction and proliferation of Turkish. As primary data collection means, a questionnaire form was developed in line with the available literature (Yiğit 2001, Valieva Erhanova 2013, Soydan 2012, Mominkulov 2013, Mihalakapoulos 2013, Karahan 2012, Akgün 2010, Adak 2004). Expert opinion was obtained for its validity and the questionnaire was applied to 157 people by a face-to-face interview method. The compliance of social variables with normal distribution has been examined with Kolmogorov-Smirnov Test. As a result of Kolmogorov-Smirnov Test, dimensions with alpha (Î±) value before p=0,05 is subjected to non-parametric tests (Mann-Whitney U and Kruskal Wallis H). Mann Whitney U test was used in paired comparisons of the variables with significant Kruskal Wallis test result. Frequency and percentage values of the obtained data were calculated and statistical analyses were done. Apart from that, experiences and observations obtained during four years spent in Kazakhstan were also used. Population of the study consists of 375 trainees at the Turkish Education Centre of the Turkish Consulate General in Almaty in January, February and March in the academic year of 2013-2014. The following formula was used in calculating the sample size in the study as the number of individuals in the target audience is known (Baş 2006:42). n = Nt²pq/d² (N-1) + t²pq In this formula; N: number of individuals in the target audience n: number of individuals to be included in the sample p: frequency of occurrence of the studied case (probability to occur) q: frequency of non-occurrence of the studied case (probability not to occur) t: theoretical value found according to the table t in a certain level of significance d: sampling error accepted according to the frequency of occurrence of the studied case Study population is assumed to be 375 persons and the sample size is found to be 157 when it is calculated in the reliability range of 95% and by a sampling error of 6% for the (Î± =0,05), p=0,5 and q=0,5 and t=1,96 values. 157 questionnaires were applied in the study and required sampling size was achieved. When selecting this sample, assumptions like all trainees were voluntary to learn Turkish at the centre and therefore had no prejudices against Turkey, Turks and Turkish to ensure that they could provide more correct and objective answers. This is one of the most important requirements to ensure health outcomes are reached by the study. In addition, it is highly probable that trainees coming to the centre based on their interest in Turkish would be watching Turkish TV series. As the study is based on Turkish TV series, individuals not watching the TV series are excluded from the study sample. Results and recommendations: This questionnaire study conducted in Almaty, the capital and the biggest and liveliest city of Kazakhstan, revealed that Turkish TV series were intensively watched in Kazakhstan not only by the Kazakh Turks but also all of the population of the country which consists of various ethnic elements. Apart from that, observations showed that TV series produced in Turkey are more popular among people from Turkish origin. The ethnical, religious and cultural closeness between these communities and Turkish society has an absolute influence in this matter. This is indicated by the fact that participants whose native languages are either Kazakh, Uzbek and Uigur find Turkish and Kazakh culture closer than those who speak Russian (see Table 10). Choosing Turkish Education Centre of the Republic of Turkey General Consulate in Almaty resulted in participants who are less than forty years by 62% and university graduates by majority. Meanwhile, these values look parallel to the general data of Kazakhstan in this matter.¹ Similarly, the ethnic distribution of participants is from Kazakh, Russian and other elements according to the quantity. The findings showed that the Turkish TV series increased the interest in Turkey, Turkish culture and language and affected the people in terms and language and culture. The percentage of positive responses in this field is high. For example, the statement â€œTurkish TV series created an interest to learn Turkishâ€ was responded by the answer â€œYesâ€ by 94,4% (see Table 3). Around 92% of the participants watch TV series in romantic, drama and comedy genres while action genre is watched by 8%. Having such a result is greatly influenced by the fact that viewers are mainly women. In addition, almost half of the participants watch TV series through Kazakhstan channels, 42,4% of the rest watch through the internet and 11,5% watch through satellite. Majority of participants watch TV series in Turkish, similar number watches in Russian and 18% watch in Kazakh language. The result that TV series are mostly watched in original language corresponds to the result that around 55% of the participants watch through the Internet. The desire of mainly university graduates to learn Turkish is effective in having such a result. In addition, we believe that TV series are watched through the Internet in the original languages mainly because the fact that dubbing quality of the TV series is very low and that the original dubbing is heard mixing with the translation which reduces the enjoyment of watching. It is also remarkable, especially for Kazakh population, that Kazakh language has a low percentage of 18,2% among the languages to watch the TV series. As a result, today media and especially television cannot be considered separately from the concept of culture and it is a producer of culture. Nations who wish to promote, spread and infuse their own culture to both their nation and the world should benefit from this power of television. What is more, it is an obligation to benefit from television in order to resist to the pressure and effects of global culture and to market own culture. Turkey has a chance of using the leverage of â€œTurkish TV seriesâ€ which have been tried and successful in the last ten years. However, considering the content of the TV series, it is observed that there is no purpose or concern to promote and spread Turkish culture and that the main objective is to ensure high profit. In this context, it is evident that state should take more initiatives in this matter. Recently, there have been many complaints pronounced regarding the content of TV series. Official authorities of Kazakhstan opted to take some measures in line with the national interests of the Kazakh people. In this sense, Muhtar Kul-Muhammad, the Kazakh Minister of Culture and Information, said the state televisions would not purchase TV series from Turkey and Korea anymore and this resource would be spent for the development of national cinema and TV series (Koskina 2013). In addition, in joint forums with Turkish originate people or in some researches on Central Asia, representatives of Kazakhstan stated that the â€œTurkish TV series do not fully reflect the reality of Turkey and the topics are not parallel to the Turkish family structure, traditions and moral qualitiesâ€ and it is desired that â€œTV series should include more topics to promote own values of Turkey and to inform the youthâ€ (Dağcı& Osmanov 2005: 12). In addition, it is stated that â€œmajority of positive characters has evil qualities, they smoke and drink alcoholâ€ (Abişev 2010: 62). What is strange is that, although these TV series are both commercial and cultural export â€œproductsâ€, no official bodies have information about when, how many, how much time of these products are sold to which country, what is the import income from these sales, or at least they don't share this information with the public.2 However, this data should be determined and statistics should be kept so that a political, commercial and cultural route map will be arranged with respect to TV series that achieved certain effectiveness even in the foreign policy of Turkey. The results of a sociological research done by ORSAM (Middle East Strategic Researches Centre) in order to reveal the perception on Turkey and Turkish nation in Kazakhstan in 2012 (Mominkulov 2013) confirm the results we obtained from this study. To conclude, more comprehensive further studies on this matter are needed to be done by sociologists.